Caracterização de um Antígeno Rico em Prolina(PRA/Ag2) do fungo patogênico humano Paracoccidioides brasiliensis - CASTRO, Kelly Pacheco de (2008)
The dimorphic fungus Paracoccidioides brasiliensis is the causative agent of the most frequent systemic mycosis in Latin America. In humans, infection starts by inhalation of fungal propagules, which reach the pulmonary epithelium and differentiate into the yeast parasitic phase. Here we describe the characterization of a proline-rich protein (PRA/Ag2) homologue of P. brasiliensis, a predictable cell wall protein, first identified in Coccidioides immitis. The protein, the cDNA and genomic sequences were analyzed. Southern blot analysis suggested that there is one copy of the gene in P. brasiliensis. The cloned cDNA was expressed in Escherichia coli and the purified rPbPRA/Ag2 was used to obtain polyclonal antibody. The purified recombinant protein was recognized by sera of patients with proven paracoccidioidomycosis and not by sera of healthy individuals. Immunoelectron microscopy and biochemical studies demonstrated the presence of PbPRA/Ag2 in the fungal cell wall, linked through a GPIanchor. The expression of the Pbpra/ag2 gene was analyzed by real time PCR and results demonstrated developmental regulation in phases of P. brasiliensis, with a higher expression in the mycelium saprobic phase. The protein expression analyses corroborate the transcript levels.